Efficacy of intravenous immunoglobulin (IVIg) on COVID-19-related neurological disorders over the last 2 years: an up-to-date narrative review - Manganotti, Paolo; Garascia, Gabriele; Furlanis, Giovanni; Buoite Stella, Alex (Frontiers in Neuroscience, 2023)
Introduction Among the clinical manifestations of SARS-CoV-2 infection, neurological features have been commonly reported and the state-of-the-art technique suggests several mechanisms of action providing a pathophysiological rationale for central and peripheral neurological system involvement. However, during the 1st months of the pandemic, clinicians were challenged to find the best therapeutic options to treat COVID-19-related neurological conditions. Methods We explored the indexed medical literature in order to answer the question of whether IVIg could be included as a valid weapon in the therapeutic arsenal against COVID-19-induced neurological disorders. Results Virtually, all reviewed studies were in agreement of detecting an acceptable to great efficacy upon IVIg employment in neurological diseases, with no or mild adverse effects. In the first part of this narrative review, the interaction of SARS-CoV-2 with the nervous system has been discussed and the IVIg mechanisms of action were reviewed. In the second part, we collected scientific literature data over the last 2 years to discuss the use of IVIg therapy in different neuro-COVID conditions, thus providing a summary of the treatment strategies and key findings. Discussion Intravenous immunoglobulin (IVIg) therapy is a versatile tool with multiple molecular targets and mechanisms of action that might respond to some of the suggested effects of infection through inflammatory and autoimmune responses. As such, IVIg therapy has been used in several COVID-19-related neurological diseases, including polyneuropathies, encephalitis, and status epilepticus, and results have often shown improvement of symptoms, thus suggesting IVIg treatment to be safe and effective.